Non-viral nucleic acid therapeutics: Revolutionizing the landscape of atherosclerotic treatment. (August 2022) - Qu, Shuai; Liu, Renfa; Zhang, Nisi; Xu, Yunxue; Yue, Xiuli; Dai, Zhifei
Abstract: Atherosclerosis is an important pathological basis of several cardiovascular diseases and viewed as a fundamental indicator for cardiovascular disease management. Gene therapy is expected to be a very promising approach to treat atherosclerosis. The past few years have seen the approval of several non-viral nucleic acid therapeutics by US Food and Drug Administration (FDA), including Inclisiran, a lipid-lowering RNA drug for atherosclerosis. Compared with viral gene vectors, non-viral nucleic acid therapeutics, especially the RNA therapeutics, is advantageous in several aspects, including low immunogenicity, almost no unwanted genomic integration, high payload size, facile in upscaling manufacturing, etc. Here, we reviewed recent advances in targeted non-viral nucleic acid delivery for gene therapy of atherosclerosis. We first described the hepatocyte-targeted nucleic acid delivery platform technologies for lipid-lowering atherosclerotic therapy. Then we summarized the advances of nucleic acid delivery targeting cells located in the atherosclerotic plaque, including endothelial cells, monocytes, macrophages and vascular smooth muscular cells. This review provides a comprehensive view and roadmap for general readers working in this field. Graphical Abstract: ga1 Highlights: Recent advances in targeted non-viral nucleic acid delivery for gene therapy of atherosclerosis are summarized. Gene therapy of atherosclerosis can be achieved by targeting hepatocytes or cells located in atherosclerotic plaque. Development of non-viral nucleic acid therapeutics will revolutionize the treatment of atherosclerosis.